MOHAMMAD NATSIR (ISLAM DAN DEMOKRASI) - Ibrahim, Sidik (Institut Agama Islam Negeri (IAIN) Palu, 2006)
This article tries to interprete some aspects of Natsirâs political thoughts, particularly that of relationship between religion and politics, with more emphasis on relationship between religion and democracy (freedom of thought), as well as relationship between religion and state. Muhammad Natsirâs political thought isÂ concerned not only with normative doctrines and theories or Islamic conceptualization in the field of politics but also with the response to poltical facts and problems of Indonesia. In his view, in Islamic democracy, the formulation of political, economic, legal policie, etc. must refer to the Islamic principles, that is the Qurâan and the prophetâs traditions (sunnah) or at least they are not in contradiction Â to the Islamic perinciples.Â Kata Kunci: Mohammad Natsir, Islam dan Demokrasi